METHODOLOGY FOR THE DEVELOPMENT OF MORAL QUALITIES OF STUDENTS THROUGH THE INTEGRATION OF NATIONAL VALUES IN THE PROCESS OF HIGHER EDUCATION - Ponsotova Feruza Uktamovna (Innovate Conferences, 2025)
This article will highlight the theoretical and practical aspects of the methodology for the development of moral qualities of students based on the integration of national values into the content of academic disciplines in the process of Higher Education. In the formation of moral qualities such as patriotism, humanity, responsibility, honesty, tolerance in students, pedagogical opportunities of national traditions and traditions, historical heritage and spiritual values are revealed. Interactive methods, project-based training, and ways to use problematic educational technologies are also recommended.
Keywords: national values, moral qualities, integration, higher education, upbringing, methodology, spiritual development.